2012
DOI: 10.1007/s11136-012-0326-0
|View full text |Cite
|
Sign up to set email alerts
|

Well-being in mothers of children with congenital heart defects: a 3-year follow-up

Abstract: The findings suggest a pattern in which all stressors concerning the severely ill child lead to significant deterioration of maternal well-being. Having a child with mild or moderate CHD, which is a less severe and shorter-term stressor, did not reduce mothers' well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Close to 50% of families of children with special healthcare needs (CSHCN) experience some type of financial burden, but the magnitude of financial impact of CHD on families is not well documented. Increased risk of caregiver psychological distress, particularly around critical periods of illness such as diagnosis and surgery, persisting up to three years after the newborn period has been documented . Very little information exists, however, on the need for mental health services.…”
Section: Introductionmentioning
confidence: 99%
“…Close to 50% of families of children with special healthcare needs (CSHCN) experience some type of financial burden, but the magnitude of financial impact of CHD on families is not well documented. Increased risk of caregiver psychological distress, particularly around critical periods of illness such as diagnosis and surgery, persisting up to three years after the newborn period has been documented . Very little information exists, however, on the need for mental health services.…”
Section: Introductionmentioning
confidence: 99%
“…Investigating risk factors for maladjustment in children and parents, severity of CHD was mainly related to more negative consequences for psychological adjustment for both the child ( 5 , 11 ) and its mother ( 12 , 13 ). Investigating surgery-related factors, associations of child psychological maladjustment with age at surgery ( 7 ) and cardiopulmonary bypass duration ( 6 ) have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, former studies predominantly combined different defects resulting in a heterogeneous sample group [e.g., Ref. ( 11 , 12 , 21 , 22 )]. In order to better understand the long-term consequences of the surgery of an isolated VSD, the current study extends existing literature about child and parent psychological adjustment to physiological measures.…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies have shown that providing care to children with neurological problems reduces maternal health levels (29)(30)(31)(32)(33)(34) . The loss of self-care is associated with the fact that they are solely responsible for the demands of the family, the socioeconomic status of these women was also a limiting factor for the establishment of healthy behaviors, such as minimally adequate food and intervals of sleep and rest.…”
Section: Discussionmentioning
confidence: 82%